Serial Bone Scintigraphy for Assessing the Effectiveness of Treatment of Osseous Metastases from Prostatic Cancer - Langhammer, H.; Sintermann, R.; Hör, G.; Pabst, H.W. (Nuklearmedizin - NuclearMedicine, 1978)
130 serial bone scintigrams were performed to evaluate the course of skeletal metastases under treatment in 36 patients with prostatic cancer. During a successful treatment scintigraphic controls revealed a significant decrease of the metastatic 99mTc-diphosphonate uptake in 14 patients and sometimes even a complete normalization of the skeletal radioactivity distribution, whereas a progression characterized by an increased multifocal radioactivity concentration was registered in 16 patients indicating the failure of the initiated therapy. Based on these results of follow-up studies scintigraphic bone imaging can be recommended for the assessment of the effectiveness of on-going therapy of skeletal metastases.